Organized crime as a link between inequality and corruption - Soeren C. Schwuchow (European Journal of Law and Economics, 2023)
We study a model that establishes a novel theoretical rationale for the empirically well-documented relation between inequality and corruption. According to our model, inequality can nurture corruption by empowering organized crime because collusion between local police forces and criminal organizations is more likely in societies characterized by high inequality or weak security forces. Law enforcement and organized crime have a strong incentive to collude due to efficiency gains from specialization. However, their agreement breaks down when the mobsters can no longer credibly commit to joint rent maximization and thus start to compete with law enforcement for citizens' wealth. The mobsters then non-violently monopolize the market for extortion by undercutting the police forces, similar to a strategy of predatory pricing. Criminal collusion is thus not very different from its corporate equivalent; hence, similar policy measures should be promising. In addition, our model also suggests that the criminal organization's higher efficiency in extracting rents has a greater impact when the relative power between law enforcement and organized crime is rather balanced. Accordingly, when violent conflict becomes less predictable, non-violent elements of relative power become more relevant. Our model also allows for the interpretation that in the absence of strong social norms against corruption, organized crime is more difficult to challenge.
Keywords: C72; D31; D63; D73; H42; K14; K42; 340; Inequality; Corruption; Organized crime; Public security